2019
DOI: 10.1088/1757-899x/589/1/012021
|View full text |Cite
|
Sign up to set email alerts
|

3D-printed polyether ether ketone samples mechanical properties estimation

Abstract: This paper is dedicated to study of mechanical characteristics (tensile limit, elasticity modulus and relative elongation) of samples made of polyether ether ketone by additive method FDM (FFF). The paper includes results of mechanical tests on tension of sample party and comparison to results of other authors. Conclusions on reasons of the results obtained are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 20 publications
1
8
0
1
Order By: Relevance
“…These tendencies were observed in the static three-point bending and uniaxial tensile tests. According to [31][32][33], our results obtained for amorphous-form samples are similar. The tensile strength had the same level of value, at about 40 MPa, but the modulus of elasticity was different due to the filling ratio.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…These tendencies were observed in the static three-point bending and uniaxial tensile tests. According to [31][32][33], our results obtained for amorphous-form samples are similar. The tensile strength had the same level of value, at about 40 MPa, but the modulus of elasticity was different due to the filling ratio.…”
Section: Discussionsupporting
confidence: 77%
“…An analysis of literature sources [ 31 , 32 , 33 ] also showed the possibility of correcting the exemplary printing modes with the aim to improve their mechanical properties. However, the conducted research provided new information on the influence of the printing positions, structure, and chemical parameters of specimens on the properties of the printed PEEK.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… Void fraction calculated from CT Scan as a function of the printing orientation and scan location [ 110 ]. …”
Section: Figurementioning
confidence: 99%
“…Other works have demonstrated potential in the manufacturing industry for FFF parts. 159 To obtain PEEK parts with the highest tensile strength, it was suggested that they be printed with 100% inll and at an inll direction of AE45 . If PEEK were adapted to the manufacturing industries in FF, modications would be required since the current strength of cast materials are 1.3 times greater.…”
Section: Polyether-derived Polymersmentioning
confidence: 99%